A Reflection on Uganda’s Foreign Policy and Role at the UN Security Council - Tabaire, Bernard; Okao, Jackie (ACODE, 2010)
"Uganda is a landlocked country that depends on foreign imports for most of its consumer goods and energy requirements. Thus, even before independence, maintaining an open trade route to the Indian Ocean was a primary foreign policy objective. Indeed, in the first decade of independence, policymakers emphasised co-operation with Uganda’s neighbours. At continental level, it assumed a pan-Africanist stance, being a founding member of the Organisation of African Unity (now African Union) and a strong supporter of liberation movements especially in Southern Africa. On the global stage, the country maintained a posture of non-alignment although it sometimes sided more with the communist/socialist bloc led by the then-Soviet Union and China. When the NRM came to power in 1986, the new government enthusiastically supported international and especially African co-operation but conditioned it on an ideological evaluation of whether other regimes were racist, dictatorial, corrupt, or violators of human rights. In a new assertiveness, Uganda actively supported the overthrow of governments in Rwanda and D.R. Congo (then Zaire) because they were dictatorial, corrupt, and abused human rights."
Keywords: Security Council; Reflection; Uganda’s Foreign Policy